BIOLOADS AND ENZYME ACTIVITIES OF PETROLEUM POLLUTED EFE RIVER WETLAND, UMULOLO, OKIGWE, IMO STATE. NIGERIA. - C. C., Ike, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
The study investigated bioloads and enzyme activities of petroleum polluted Efe River wetland. The bioloads and trend of enzymatic activities in petroleum polluted and unpolluted wetlands were evaluated using standard methods. Bioloads for all microbial groups enumerated, had highest values during rainy season when compared with dry season counterpart. Total viable count (TVC) had highest counts in the lightly polluted wetlands – rainy/ dry seasons (3.9 ±0.19) x 105 , (3.2 ±0.21) x 105, followed by control “unpolluted wetlands” (3.4 ±0.17) x 105 , (2.8 ±0.16) x 105 and lowest values in the heavily polluted wetlands (3.3 ±0.23) x 103 , (2.8 ±0.29) x 103 respectively. The same trend was observed with other microbial groups assessed. Bacillus species was the most prevalent for both seasons - lightly polluted wetlands – rainy/ dry season (87.5% ±0.11/ 75% ±0.16), heavily polluted wetlands (50% ±0.32/ 25% ±0.15), and control “unpolluted wetlands” (75% ±0.14/ 62.5% ±0.24). The values of soil enzymatic activities followed the same trend with bioloads. Dehydrogenase enzyme (µg TPF g-1 hr-1 ) activities recorded very high values (4658 ±57) in the assessed wetlands, unlike alkaline phosphatase enzyme that had the least values (82.67 ±1.12). High values of enzymatic activities were observed in lightly polluted wetland, followed by control (unpolluted wetland) and heavily polluted wetland in that order. All values obtained in bioloads, prevalence and enzymatic activities, when compared were statistically significant (p<0.05). This study has shown that petroleum on heavy impaction could cause negative effects on wetlands bioloads and enzyme activities while light impaction encourages bioloads replication and increased enzyme activities resulting in improved indicator values.